Networking in the nucleus: a spotlight on LEM-domain proteins. (June 2015) - Barton, Lacy J; Soshnev, Alexey A; Geyer, Pamela K
Abstract : Proteins resident in the inner nuclear membrane and underlying nuclear lamina form a network that regulates nuclear functions. This review highlights a prominent family of nuclear lamina proteins that carries the LAP2-emerin-MAN1-domain (LEM-D). LEM-D proteins share an ability to bind lamins and tether repressive chromatin at the nuclear periphery. The importance of this family is underscored by findings that loss of individual LEM-D proteins causes progressive, tissue-restricted diseases, known as laminopathies. Diverse functions of LEM-D proteins are linked to interactions with unique and overlapping partners including signal transduction effectors, transcription factors and architectural proteins. Recent investigations suggest that LEM-D proteins form hubs within the nuclear lamina that integrate external signals important for tissue homeostasis and maintenance of progenitor cell populations.